2014
DOI: 10.4196/kjpp.2014.18.4.347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Watercress Containing Rutin and Rutin Alone on the Proliferation and Osteogenic Differentiation of Human Osteoblast-like MG-63 Cells

Abstract: Most known osteoporosis medicines are effective for bone resorption, and so there is an increasing demand for medicines that stimulate bone formation. Watercress (N. officinale R. Br.) is widely used as a salad green and herbal remedy. This study analyzed a watercress extract using ultra-performance liquid chromatography/mass spectrometry, and identified a rutin as one of its major constituents. Osteogenic-related assays were used to compare the effects of watercress containing rutin (WCR) and rutin alone on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Based on these data, renal tubular ischemia due to the oxidative effects of VCM is the main known mechanism of VIN (5,12,13). ditional medicine, the leaves of the plant are widely used as diuretic, expectorant, blood purifier, hypoglycemic, and odontolgic (14)(15)(16)(17). Yazdanparast and colleagues reported that watercress supplementation in diet decreases serum lipids and alters blood antioxidant status in hypercholesterolaemic rats (18).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these data, renal tubular ischemia due to the oxidative effects of VCM is the main known mechanism of VIN (5,12,13). ditional medicine, the leaves of the plant are widely used as diuretic, expectorant, blood purifier, hypoglycemic, and odontolgic (14)(15)(16)(17). Yazdanparast and colleagues reported that watercress supplementation in diet decreases serum lipids and alters blood antioxidant status in hypercholesterolaemic rats (18).…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts have been used to treat cancers due to their effective anticancer properties [14]. In addition to the anti-cancer effects, various plant extracts have also been studied for its proliferation and differentiation effects of stem cells [15][16][17]. Watercress with the botanical name Nasturtium officinale is a perennial European herb of the family Cruciferae (mustard family) that grows in freshwater streams.…”
Section: Introductionmentioning
confidence: 99%
“…Watercress is rich in potent antioxidants, vitamins, iodine, calcium, iron, manganese and isothiocyanates [18,19]. Moreover, it has been reported to have numerous medicinal effects including antimicrobial, diuretic, antihypertensive, anti-diabetes, anti-cancer and particularly for it's antioxidant and anti-inflammatory properties [16,18,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to quercetin, rutin increases mMSCs proliferation at the high dose of 400 μM and induces osteoblastic differentiation by enhancing ALP activity, expression of important osteoblastic differentiation markers, and some degree of mineralization (Srivastava et al ., ). Also, rutin could induce proliferation and differentiation of MG‐63 cells at the concentrations of 10 and 25 μg/mL without any cytotoxicity effect (Hyun et al ., ). This result suggests that watercress and its main compound, rutin, are useful in inducing the osteoblastic activity, which in turn causes bone regeneration via synthesis of Col‐1 and enhancing the activity of ALP.…”
Section: Effects Of Phytochemicals On the Dynamics Of Stem Cellsmentioning
confidence: 97%
“…Rutin (quercetin‐3‐ O ‐rutinoside), which is abundant in vegetables such as watercress, as a dietary glycoside, possesses vasoconstrictive effects and prevents inflammation and ovariectomy‐induced osteopenia (Hyun et al ., ; Pourhassan‐Moghaddam et al ., ). Similar to quercetin, rutin increases mMSCs proliferation at the high dose of 400 μM and induces osteoblastic differentiation by enhancing ALP activity, expression of important osteoblastic differentiation markers, and some degree of mineralization (Srivastava et al ., ).…”
Section: Effects Of Phytochemicals On the Dynamics Of Stem Cellsmentioning
confidence: 99%